Common Risk Factors of Myocardial Infarction and Some Socio Demographic Characteristics in Sulaimani City - Sharif, Bayan Omar; Lafi, Samir Y. (Kurdistan Journal of Applied Research, 2022)
Back ground: Coronary heart disease is one of the vital causes of morbidity and death in Iraq. Socioeconomic status is also affected by coronary heart disease. These risk factors in Sulaimani city of Iraq is remain uncertain. This is a shortage of study of master student. The current study’s main aims were to explore the potential association between several predisposing factors and heart attack in Sulaimani, Iraq, and to some socio demographic in this participant. 165 contributors who were attending to the Cardiac Specialty Hospital, (Coronary Care Unit), and they were definitely diagnosed as having MI participated in the current study between 2015 and 2016; in Sulaimani, Iraq. The study was attentive on exploring the socioeconomic status, lifestyle, family history of heart attack and classical predisposing factors such as (Hypertension, Diabetes Mellitus, smoking cigarette, and dyslipidemia). For collecting the data, the questionnaire was designed according reading literature and books. The tests of Kolmogorov–Smirnov, Pearson and Spearman were used for the current data analysis. The finding: patients at the age of ?61 years was a common group age for myocardial infarction. Sedentary lifestyle (81.8%) and smoking (Ex- passive and current smoking 69.7% was predominance. The prevalence of BMI > 25 was (75.15%). Hypertension accounted (61.2%), dyslipidemia (39.4%), and diabetes (20%) of the subjects. A positive first-degree history of classical MI risk factor of the participants was (54.5%, 39.2% and 28.4%) for hypertension, heart attack and diabetes, respectively. (98.2%) of the selected patients no eating fish. (56.4%, 58.8%) of them were not eating daily fruit and vegetable respectively. Smoking was significant correlation with age, gender, level of education, and marital status (r = 0.34, 0.38, -0.23 and 0.17) respectively) (p value less than 0.05). Conclusions: In Sulaimani city of Iraq the strong predictors of heart attack were included: sedentary lifestyle, high body mass index, positive family history, unhealthy diet, smoking cigarette, high blood pressure, dyslipidemia, and Diabetes Mellitus.